Focus on the activity of local ethic committees in Italy (Italian Journal of Public Health, 2008)
Background: The continuing evolution of medical treatments and the loss of neutrality of medicine withrespect to morality of human values have represented the major tracking elements towards settings ofsharing of choices between society and medicine. Several concerns have been raised upon links betweenpharmaceutical corporations and researchers. Moreover, being in a learning environment, we must pay evenmore attention to these items because students appear to be at risk for unrecognized influence by marketingefforts. The aim of this study is to focus on the activities of a local ethics committee (LEC) and thecharacteristics of the protocols discussed in an Italian LEC during a three year period (2001-2003).Methods: Three years of activity of a LEC were analysed by a questionnaire registering: main sponsorship,setting, technical characteristics of trials, outcome of the submission to the LEC, state of progress. Approvedtrials were followed-up until April 30th, 2005.Results: A total of 345 protocols were discussed. 67.8% (n = 198) of approved protocols were submitted by apharmaceutical corporation. 72.6% (n = 212) of studies approved in 2001 were still in progress in 2005. 91.3%(n = 73) of closed trials had a pharmaceutical corporation as their main sponsor. None of the submittedstudies focused on prevention strategies.Conclusions: These results show how important grants offered by pharmaceutical industries are, the effortsspent on therapy and the lack of investors in prevention.
Keywords: ethic committees; ethics; research; research supports